2017
DOI: 10.1371/journal.pone.0175700
|View full text |Cite
|
Sign up to set email alerts
|

What are the prospects for citizen science in agriculture? Evidence from three continents on motivation and mobile telephone use of resource-poor farmers

Abstract: As the sustainability of agricultural citizen science projects depends on volunteer farmers who contribute their time, energy and skills, understanding their motivation is important to attract and retain participants in citizen science projects. The objectives of this study were to assess 1) farmers’ motivations to participate as citizen scientists and 2) farmers’ mobile telephone usage. Building on motivational factors identified from previous citizen science studies, a questionnaire based methodology was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 54 publications
4
80
0
1
Order By: Relevance
“…The engagement of farmers in the research process provides a cost-efficient way to collect data at a broader scale. Recent studies highlight the potential of citizen science methodology to improve farmers knowledge in developing countries [12,44] and to promote agricultural sustainability in areas that lack extension programmes [6,12]. Beyond that, citizen science can be particularly useful to address groups of farmers who have not been in the focus of experimental research, such as horse farmers.…”
Section: Citizen Science As a Research Methodology In Horse Husbandrymentioning
confidence: 99%
See 1 more Smart Citation
“…The engagement of farmers in the research process provides a cost-efficient way to collect data at a broader scale. Recent studies highlight the potential of citizen science methodology to improve farmers knowledge in developing countries [12,44] and to promote agricultural sustainability in areas that lack extension programmes [6,12]. Beyond that, citizen science can be particularly useful to address groups of farmers who have not been in the focus of experimental research, such as horse farmers.…”
Section: Citizen Science As a Research Methodology In Horse Husbandrymentioning
confidence: 99%
“…Engaging farmers in research projects provides a prospect to learn from and to empower those who manage our agricultural landscapes. In contrast to amateur naturalists, for whom participation in citizen science is usually a leisure-time activity, farmers' engagement in research activities is often linked to the benefit they obtain for their own enterprise [12]. Farmers already successfully collaborate with scientists in farm-based participatory action research (PAR), such as farm networks or on-farm trials.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that alternative methods of farmer involvement that occur over longer time periods, such as crowd sourcing and citizen science, may increase farmer engagement and improve self-reported accuracy (Beza et al, 2017;van Etten et al, 2019). For example, previous studies have shown that farmers in smallholder systems can be motivated to participate as citizen scientists throughout a research project by providing benefits to the farmers, including information sharing, agronomic advice, capacity building, and new seed varieties (Beza et al, 2017). Future work should examine whether such efforts to increase farmer engagement in data collection improve selfreported accuracies.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying ways to increase self-reported accuracy could be extremely beneficial for collecting high-quality, low cost ground data that could be used to calibrate and validate remote sensing algorithms at large spatial and temporal scales. Previous studies have suggested that involving farmers as stakeholders in the research process may be one way to increase self-reported accuracies (Beza et al, 2017). The use of citizen science is one such example where involving farmers has been shown to successfully improve the accuracies of self-reported data (van Etten et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The wide availability of smartphones, tablets, desktop computers, and easy access to the internet in more developed countries is enabling the public to record environmental data in many more locations and at finer timescales, complementing professional monitoring programmes. In contrast, citizen science projects reliant on technology, including access to the internet and mobile coverage, have limited success in resource‐poor countries where they have to compete with other priorities for scarce resources (Beza et al, ; Braschler, ). Although some notable examples exist (see Table SI), the primary barriers to citizen river science in less developed countries include limited awareness of opportunities; limited organisational capacity, including planning, leadership, and coordination; lack of appreciation of the value of citizen science from decision makers; lack of skilled participants; inadequate funding; and limited incentives (see Pocock et al, ).…”
Section: The Rise Of Citizen Science and Citizen River Sciencementioning
confidence: 99%